2014
DOI: 10.4103/0972-0707.144604
|View full text |Cite
|
Sign up to set email alerts
|

Investigate the correlation between clinical sign and symptoms and the presence of P. gingivalis, T. denticola, and T. forsythia individually or as a "Red complex" by a multiplex PCR method

Abstract: Aim:The aim of this study was to investigate the correlation between endodontic clinical signs and symptoms and the presence of Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia or their association by Multiplex polymerase chain reaction assay.Materials and Methods:Microbial samples were taken from 30 cases with necrotic pulp tissues in primary infections. DNA was extracted from the samples, which were analyzed for the presence of three endodontic pathogens by using species-specific prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…While the other protective signaling pathways prevent cells from apoptosis, a number of studies found that PI3K-AKT pathway plays an important role in preventing cell apoptosis. Recent studies have revealed that AKT has direct inhibitory effects on apoptotic Bcl-2 family proteins [21]. We also reported that the PI3K-AKT pathway was an activated response to severe burns in rats; however, the function of the activated PI3K-AKT pathway in hypoxic cardiomyocytes simulating burns remains unclear.…”
Section: Discussionmentioning
confidence: 81%
“…While the other protective signaling pathways prevent cells from apoptosis, a number of studies found that PI3K-AKT pathway plays an important role in preventing cell apoptosis. Recent studies have revealed that AKT has direct inhibitory effects on apoptotic Bcl-2 family proteins [21]. We also reported that the PI3K-AKT pathway was an activated response to severe burns in rats; however, the function of the activated PI3K-AKT pathway in hypoxic cardiomyocytes simulating burns remains unclear.…”
Section: Discussionmentioning
confidence: 81%
“…For example, propionate was positively correlated with Tanneralla , which was significantly reduced in plaque microbiota during the product treatments ( Figs 1 d and 2 c). Propionate is a virulence factor produced by T. forsythia for immunoevasion and immunosuppression 18 19 . Alanine and glycine were used for oral bacterial cell wall-peptidoglycan synthesis 20 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Together with P. gingivalis and T. forsythia, Treponema denticola constitutes the red-complex bacteria and it has been detected in necrotic pulps associated with swelling caused by primary endodontic infections [76]. Previous research suggested that the strong synergistic association between T. denticola and P. gingivalis based on the motility of T. denticola [75].…”
Section: Discussionmentioning
confidence: 99%